Architecture and key technologies of 5G converged charging system - Lei QI; Huiqiong GU; Hao ZHU; Xu CHEN (Dianxin kexue)
To satisfy 5G network construction and business development, co-based business operations and support become an important goal of 5G support network, and the deployment strategy need to be planned.The changes in the network were analyzed, the converged charging system framework based on micro servers was designed, and the functional architecture such as billing data services and billing gateway was proposed.The key technologies such as message processing and smart quotas were introduced, multi-dimensional charging capabilities were analyzed, and the network evolution strategy was described.Applications and solutions of charging frameworks for different business scenarios were proved, a blueprint for the evolution of the CCS was provided, and the business innovation and operations were prepared.